Was There Ever a Polish Peasant? Historical Imagination and the People’s History of Poland - Mazur, Zachary (Acta Poloniae Historica, 2023)
This essay uses five new Polish-language books popularising the ‘people’s’ history perspective as a jumping-off point to discuss distortions in the historical imagination. At the centre is the issue of the peasantry. In some national mythologies, the peasants or the ‘people’ serve as the heart of the nation. In the Polish case, this has been the role of the nobility or szlachta and as a result the peasants are often forgotten or skipped over in popular historical narratives. These new books represent a sea change in historical imagination, not for the academy, but for the broader public.